2013
DOI: 10.1155/2013/254383
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Technique of Lamellar Keratoplasty (DMEK-S)

Abstract: Purpose: To evaluate the outcomes of the hybrid technique of posterior lamellar keratoplasty (DMEK-S). Materials and Methods: 71 eyes of 55 patients enrolled in a single-center study underwent posterior lamellar keratoplasty with a hybrid lamella DMEK-S implanted using a solution implantation technique, owing to endothelial dysfunction. The outcome measures studied were visual acuity and endothelial cell density. Results: The rate of endothelial cell loss caused by surgery was 43.8%. During followups, we obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Studeny et al 19 reported a high rebubble rate of 61.9% in their DMEK-S series and attributed this to retained viscoelastic in the interface and a nonsmooth transition between the peripheral stromal ring and DM. In our method here, no viscoelastic was used on the anterior side of DM, and the lamellar ring is much more uniform as it was custom-cut with an FL.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Studeny et al 19 reported a high rebubble rate of 61.9% in their DMEK-S series and attributed this to retained viscoelastic in the interface and a nonsmooth transition between the peripheral stromal ring and DM. In our method here, no viscoelastic was used on the anterior side of DM, and the lamellar ring is much more uniform as it was custom-cut with an FL.…”
Section: Discussionmentioning
confidence: 97%
“…First, they are difficult manual techniques and have been described elsewhere. 13,18,19 Methods to streamline the preparation of DMAEK may make it more available to surgeons. This novel approach offers a precise and predictable means in creating the stromal rim and in controlling big bubble expansion using an FL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations